Impact of an appendicolith and its characteristics on the severity of acute appendicitis - Sula, Sami; Paananen, Timo; Tammilehto, Ville; Hurme, Saija; Mattila, Anne; Rantanen, Tuomo; Rautio, Tero; Pinta, Tarja; Sippola, Suvi; Haijanen, Jussi M.; Salminen, Paulina (Oxford University Press, 2025)
BACKGROUND: Antibiotics have been reported as an efficient and safe treatment option for uncomplicated acute appendicitis without an appendicolith diagnosed using computed tomography (CT). The aim of this study was to assess the association of a CT-diagnosed appendicolith and its characteristics with appendicitis severity.
METHODS: A large prospective patient cohort with suspected acute appendicitis enrolled between April 2017 and November 2018 was retrospectively reviewed. The initial analysis evaluated the association of a CT-diagnosed appendicolith with complicated acute appendicitis; then, based on the availability of CT images, a subset of patients was analysed for the correlation of appendicolith characteristics with appendicitis severity. The final appendicitis assessment (uncomplicated or complicated-including perforation, gangrene, an abscess, or a tumour) was determined for all patients.
RESULTS: Out of 3512 eligible patients, 3085 patients with appendicitis were selected and 380 patients with an appendicolith and with a CT image available for reassessment were included. Out of the 3085 patients with CT-diagnosed acute appendicitis, 1101 (35.7%) patients presented with both acute appendicitis and an appendicolith and, out of these, 519 (47.1%) had complicated acute appendicitis. In the patients without an appendicolith (1984 patients), 426 (21.5%) had complicated appendicitis (P < 0.001). Re-evaluation of CT images for 380 patients showed that a larger appendicolith diameter (OR = 1.15 (95% c.i. 1.06 to 1.25); P < 0.001), appendicolith location at the base of the appendix (55.1% versus 44.9%; P = 0.008), and heterogeneous appendiceal wall enhancement around the appendicolith (68.4% versus 31.6%; P < 0.001) were associated with an increased risk of complicated acute appendicitis.
CONCLUSION: The presence of an appendicolith in patients with acute appendicitis is correlated with the risk of complicated appendicitis. This risk is further increased by a larger appendicolith diameter or appendicolith location at the base of the appendix.